2015
DOI: 10.1111/cxo.12260
|View full text |Cite
|
Sign up to set email alerts
|

Persisting extreme acute corneal hydrops with a giant intrastromal cleft secondary to keratoconus

Abstract: Acute corneal hydrops (hydrops corneae) is an incompletely understood complication of keratoconus and other corneal ectatic disorders, including keratoglobus and pellucid marginal corneal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…It has been reported that the average thickness of the keratoconic cornea is reduced to approximately 437μm centrally and 559μm towards the periphery, 17 whereas, in cases with unresolved oedema following Descemet's membrane rupture, the central cornea can be 878μm 18 or more. 19 However, our subject with keratoconus and resolved oedema provided much thinner corneal measurements at 260μm centrally and 450μm at 8mm diameter. This extreme thinning and flattening of the central cornea might be a result of the extensive rupture of Descemet's membrane.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported that the average thickness of the keratoconic cornea is reduced to approximately 437μm centrally and 559μm towards the periphery, 17 whereas, in cases with unresolved oedema following Descemet's membrane rupture, the central cornea can be 878μm 18 or more. 19 However, our subject with keratoconus and resolved oedema provided much thinner corneal measurements at 260μm centrally and 450μm at 8mm diameter. This extreme thinning and flattening of the central cornea might be a result of the extensive rupture of Descemet's membrane.…”
Section: Discussionmentioning
confidence: 66%
“…ACH is a severe complication of keratoconus, caused by disruption and local detachment of the DM ( 5 , 6 ). Due to its elasticity, DM retracts or coils when it breaks under tension, and the aqueous humor flows into the corneal stroma, causing severe corneal edema and opacity, and even leading to the formation of intrastromal clefts (pseudocysts).…”
Section: Discussionmentioning
confidence: 99%
“…Keratoconus is a chronic ectatic corneal disorder whose etiology, which seems to involve the inflammatory cascade, and is related to mechanical trauma from the habit of rubbing the eyes and nocturnal ocular compression ( 1 , 2 ), is still the subject of extensive debate, is characterized by the presence of irregular astigmatism and corneal thinning, which usually progress during the first three decades of life ( 3 , 4 ). Acute corneal hydrops (ACH), which may result in corneal scars and vision loss, is an uncommon complication of keratoconus secondary to rapid stromal edema, and even intrastromal clefts (pseudocysts) formation, secondary to Descemet membrane rupture ( 5 , 6 ). ACH is usually self-limiting and generally resolves without intervention over 2–4 months ( 7 ), and may preset complications such as neovascularization ( 8 ), infection, malignant glaucoma, and corneal perforation ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Die Wundheilung mit Ausbildung einer neuen Descemet-Membran durch migrierendes Endothel ( Abb. 2 c ) erfolgt über mehrere Wochen und kann mittels Muraine-Nähten unterstützt werden 18 . Die Neubildung der Descemet-Membran nach akutem Keratokonus mit den charakteristischerweise eingerollten Rändern im Rissbereich und einer dünnen „neuen“ Descemet-Membran findet sich sowohl bei Spontanheilung als auch nach Muraine-Nähten.…”
Section: Keratektasienunclassified
“…Wound healing with formation of a new Descemet membrane through endothelial migration ( Fig. 2 c ) takes several weeks and can be supported by Muraine sutures 18 . Reformation of the Descemet membrane after acute keratoconus, with characteristically rolled-up edges in the area of the tear and a thin “new” Descemet membrane, is observed both with spontaneous healing and after application of Muraine sutures.…”
Section: Corneal Ectasiamentioning
confidence: 99%